Comparison of Concrete Performance With Fiberglass Substitution as A Sand Replacement - yuliswidhiastuti; Soegyarto; Andy Yanuar Putra Riyadi (Journal of Green Science and Technology, 2025)
Fiberglass, with its superior mechanical properties and corrosion resistance, has been proposed as a partial or total replacement for sand in concrete mixes. Although research on the use of glass powder as a sand substitute has been widely conducted, specific studies examining the use of fiberglass as a fine aggregate replacement in concrete are limited. Therefore, this study will focus on a comparative analysis of the performance of concrete with fiberglass substitution as a sand replacement material, considering various mechanical and durability aspects. With the aim of knowing the effect of the addition of fiberglass powder into the concrete mixture. in this study the method of calculating mix design using the SNI 03-2834-2000 method. in this research, the results obtained with the addition of fiberglass in the concrete mixture at certain variations cannot increase the compressive strength of Hybrid concrete at the age of 7 days, 14 days and 28 days.   The optimum value of the 7-day concrete compressive strength test is in the 2% variation of fiberglass addition, which is 12.14 MPa because it does not decrease significantly. The optimum value of the 14-day concrete compressive strength test is also in the 2% variation of 15.01 MPa, and for the optimum value of the 28-day concrete compressive strength test is also in the 2% variation of 18.38 MPa.  Keyword: Concrete, Fiberglass, Compressive Strength.